Effect of Dog-Assisted Therapy on Psychomotor Development of Children with Intellectual Disability - Wolan-Nieroda, Andżelina; Dudziak, Jadwiga; Pniak, Bogumiła; Druzbicki, Mariusz; Guzik, Agnieszka (My University, 2020)
Background: Although dog-assisted therapy (DAT) has been used for years, there is still a scarcity of research findings confirming efficacy of the method. The current study was designed to assess ef-fects of DAT on psychomotor development of children with mild intellectual disabilities. Material and method: The study involved 60 children with mild intellectual disabilities, aged 10–13 years, divided into a group participating in a 10-month DAT program, and the control group. Four tests were applied, i.e., finger identification, postural imitation, kinaesthesia, and Bourdon-Wiersma Dot Cancellation Test. The examinations were carried out before the start and at the end of the DAT, and at a two-month follow-up. Results: The results obtained by the DAT group in all the four tests, at all the three timepoints, were not the same (p < 0.001). No statistically significant differences were found in the measurement at the end of the therapy between the DAT group and the controls. On the other hand, the DAT group achieved significantly better scores (p = 0.001 and p = 0.001), compared to the control, in the follow-up measurements two months after the end of the therapy in postural imitation and finger identification tests. Conclusions: Some of the scores achieved by the children in the DAT group improved in the measurements performed over time. Two months after the therapy ended, the children in the DAT group presented greater gains in motor planning (postural imitation test) and in the sense of touch, attention, and concentration (finger identification test), compared to the control group. Although the measurement performed immediately after the therapy did not show significant differences between the DAT group and the controls, the exam-ination carried out at the two-month follow-up identified long-term gains in the treatment group in the domain of motor planning (postural imitation test).
Keywords: dog-assisted therapy; intellectual disability; psychomotor disorders; child developmental; kines-thesis; cognition disorders; dogs